2021
DOI: 10.1128/mbio.00904-21
|View full text |Cite
|
Sign up to set email alerts
|

ColdZyme Maintains Integrity in SARS-CoV-2-Infected Airway Epithelia

Abstract: Although our understanding of COVID-19 continuously progresses, essential questions regarding prophylaxis and treatment remain open. A hallmark of severe SARS-CoV-2 infection is a hitherto-undescribed mechanism leading to excessive inflammation and tissue destruction associated with enhanced pathogenicity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 32 publications
(51 reference statements)
0
28
0
Order By: Relevance
“…As recently shown, ColdZyme® mouth spray effectively blocked binding, uptake and infection of SARS-CoV-2 wildtype in a human respiratory model that was associated with rescue to tissue integrity and from excessive innate immune activation [ 9 ]. ColdZyme® is a Class III medical device (CE-marked) composed of glycerol, water, buffer, CaCl2, menthol and trypsin from the Atlantic cod ( Gadus morhua ) [ 10 ] (ClinicalTrials.gov, ID: NCT03901846).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As recently shown, ColdZyme® mouth spray effectively blocked binding, uptake and infection of SARS-CoV-2 wildtype in a human respiratory model that was associated with rescue to tissue integrity and from excessive innate immune activation [ 9 ]. ColdZyme® is a Class III medical device (CE-marked) composed of glycerol, water, buffer, CaCl2, menthol and trypsin from the Atlantic cod ( Gadus morhua ) [ 10 ] (ClinicalTrials.gov, ID: NCT03901846).…”
Section: Introductionmentioning
confidence: 99%
“…Beside rhinovirus, RSV and influenza, SARS-CoV-2 as well as the common cold coronavirus HCoV-229E were demonstrated to be sensitive to prophylactic treatment with ColdZyme® mouth spray in previous in vitro analyses within various cellular systems, i.e. Vero E6 and MRC-5 cells, but also in 3D human airway epithelial tissue cultures [ 9 , 13 ]. Posch et al recently showed a robust engagement of complement in human airway epithelial (HAE) tissue cultures after viral infection, which was associated with high anaphylatoxin and pro-inflammatory cytokine release, high viral loads and excessive tissue destruction [ 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, the in vitro data are just a first step in a number of future testing—obviously, mucosal distribution, concentration, achieving a sufficiently high concentration of P80 in target cells and retention are critical parameters. As applying the P80 natural essence directly at mucosal surfaces to target DCs and LCs, the concentrations used in our in vitro setting with a range of 0.5 to 1% might be achieved in an in vivo scenario, but this needs further confirmation in an in vitro 3D mucosal tissue [ 28 , 29 ] and—If effective in murine models.…”
Section: Discussionmentioning
confidence: 99%
“…Augmenting this physical barrier with a topical spray has been suggested as one approach to reduce viral uptake. This concept is supported by in vitro data showing a reduction in SARS-CoV-2 binding to human airway epithelial cells after pre-treatment with a protease-containing glycerin barrier spray [ 5 ]; however, data confirming its efficacy in clinical trials is lacking.…”
Section: Viral Uptake and Local Upper Airway Mucosal Responsementioning
confidence: 97%